2014
DOI: 10.1111/jai.12525
|View full text |Cite
|
Sign up to set email alerts
|

Architecture, mineralization and development of the axial skeleton in Acipenseriformes, and occurrences of axial anomalies in rearing conditions; can current knowledge in teleost fish help?

Abstract: International audienceWe review current knowledge of axial skeleton biology in Acipenseriformes with the aim to know whether available data can help in understanding axial anomalies (anomalies of the vertebral column) in reared sturgeons or if further investigations are needed prior to undertake such analysis. In particular, accurate data on axial skeleton development, structure and mineralization are required to understand these pathologies. We show that such knowledge is fragmented and incomplete when compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…According to the results described here, no cartilaginous or mineralized elements were observed in the skull of A. persicus at hatching, whereas the notochord was the main skeletal element distinguishable at this stage. The lack of vertebral centra and the presence of a persistent notochord are considered as common features of the axial skeleton in the early ontogeny of sturgeons (Hilton et al ., ; Leprévost & Sire, ). The notochord is a medial structure that appears early in the embryo of all vertebrates and has several important functions in biochemical and physiological signaling (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results described here, no cartilaginous or mineralized elements were observed in the skull of A. persicus at hatching, whereas the notochord was the main skeletal element distinguishable at this stage. The lack of vertebral centra and the presence of a persistent notochord are considered as common features of the axial skeleton in the early ontogeny of sturgeons (Hilton et al ., ; Leprévost & Sire, ). The notochord is a medial structure that appears early in the embryo of all vertebrates and has several important functions in biochemical and physiological signaling (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…As Leprévost & Sire () reviewed, few morphological studies on the skeleton of Acipenseriformes are available, even though a renewed interest in sturgeon biology has recently been promoted by their commercial importance, uniqueness and almost universally endangered status (Findeis, ). This information is incomplete and fragmented in terms of species and also in terms of age; in particular, out of the 25 living acipenserid species, the skeleton of only 13 species and a hybrid has been studied and the axial skeleton is often not the main topic of such studies (Leprévost & Sire, ). Considering the unique properties of the skeleton in Acipenseriformes, including an internal cartilaginous skeleton, five rows of bony plates, ganoid scales on the body surface and lack of a vertebral centrum (Viegas et al ., , ), coupled with their distinctive skeletogenesis, it is worth investigating normal patterns of skeletal development, which will be essential to assess deformities accurately in hatchery‐produced fry, detect critical stages during skeletogenesis and improve larval rearing practices in this commercially important and endangered group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In salmonids, for instance, several studies demonstrated the link between bone mineralization and vertebral health (Deschamps, Girondot, Labbé, & Sire, ; Deschamps, Labbé, et al, ; Deschamps et al, ; Kacem & Meunier, ). In sturgeons, however, the development, mineralization and architecture of the vertebral column are poorly documented as revealed in a recent review of the literature (Leprévost & Sire, ). This lack of data led us to perform a study aiming to describe more precisely the mineralization of the vertebral column of Siberian sturgeons ( Acipenser baerii Brandt, 1869).…”
Section: Introductionmentioning
confidence: 99%
“…It is also crucial to know how deformities that occur in wild fish differ from deformities of farmed fish (Sambraus et al., ). To obtain insights into common developmental processes, the study of basal bony fish species is important (De Clercq et al., ; Leprévost and Sire, ). There is substantial progress in understanding teleost skeletal metabolism documented in the fifth section ‘Nutrition and Metabolism’.…”
mentioning
confidence: 99%